2016
DOI: 10.3389/fenvs.2016.00081
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Behavioral Changes: Using Laboratory Observations to Predict Field Observations

Abstract: Behavioral assays constitute important research tools when assessing how fish respond to environmental change. However, it is unclear how behavioral modifications recorded in laboratory assays are expressed in natural ecosystems, a limitation that makes it difficult to evaluate the predictive power of laboratory-based measurements. In this study, we hypothesized that exposure to a benzodiazepine (i.e., oxazepam) increases boldness and activity in laboratory assays as well as in field assays-that is, laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
0
29
2
Order By: Relevance
“…Susceptibility differences between species are one of the key challenges in ecotoxicology. For example, studies have shown that small wild-caught prey fish are more sensitive to the anxiolytic effects of the pharmaceutical oxazepam than are larger predatory fish or laboratory-reared fish [5,80,81]. This could be due to species differences in the rate and extent of pharmaceuticals being taken up, metabolized and concentrated.…”
Section: Problems Of Scale and Complexity: Predicting Effects In The mentioning
confidence: 99%
See 1 more Smart Citation
“…Susceptibility differences between species are one of the key challenges in ecotoxicology. For example, studies have shown that small wild-caught prey fish are more sensitive to the anxiolytic effects of the pharmaceutical oxazepam than are larger predatory fish or laboratory-reared fish [5,80,81]. This could be due to species differences in the rate and extent of pharmaceuticals being taken up, metabolized and concentrated.…”
Section: Problems Of Scale and Complexity: Predicting Effects In The mentioning
confidence: 99%
“…Research on chemical contaminants conventionally recorded a limited range of endpoints, most commonly by studying mortality following exposure in the laboratory and/ or by testing the impact of a single contaminant on a single species under standardized laboratory conditions ([4], but see [5]). These approaches are logistically tractable and repeatable but are criticized for their simplicity, particularly when such experiments neither take chemical nor biological complexity into account [6].…”
Section: Introductionmentioning
confidence: 99%
“…Whether such behavioural observations in these common fish models translate to other less commonly studied fish species ( Saaristo et al , 2017 ; Martin et al , 2017 ) or wild fish responses to neuroactive and other therapeutics or stressors represent important research needs. For example, recent studies have extended laboratory studies with a benzodiazepine (Brodin et al , 2013) to use telemetry to observe fish behaviour in the field following pharmaceutical treatment ( Klaminder et al , 2016 ; Hellström et al , 2016a , b ). Behavioural studies with invertebrates and estuarine and marine species are much less common ( Fong and Ford, 2014 ; Pyle and Ford, 2016 ), yet human populations routinely reside on or immediately upstream from coastlines.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…concentrations occurring in effluent waters entering natural systems) of one of the most commonly utilized benzodiazepines, oxazepam, have in laboratory assays been shown to affect several behavioral traits in fish, such as activity and risk taking (Brodin, Fick, Jonsson, & Klaminder, ; Klaminder, Jonsson, Fick, Sundelin, & Brodin, ). Further, effects of oxazepam on fish behavior have also been observed in natural lakes (Klaminder et al, ), raising concerns for environmental consequences.…”
Section: Introductionmentioning
confidence: 99%